Unveiling the Unconventional: Exploring Atypical Manifestations of Scrub Typhus (Indian Journal of Case Reports, 2024)
Scrub typhus is a rickettsial illness caused by Orientia tsutsugamushi. It is a common cause of undifferentiated febrile illness, especially in the Indian subcontinent, usually with multiorgan involvement, though central nervous involvement is rare. Here, we demonstrate a case of a young female who presented with fever, headache, vomiting, and seizures. Her examination was remarkable for generalized blanchable macular rash, opsoclonus–myoclonus along with neck rigidity and mild epigastric tenderness. Contrast-enhanced magnetic resonance imaging brain was suggestive of leptomeningitis. She also had mild pancreatitis, transaminitis, thrombocytopenia, and transaminitis. Given the ongoing tropical fever burden in Northern India, further workup was done and enzyme-linked immunosorbent assay anti-scrub typhus immunoglobulin M came as positive. Doxycycline along with supportive treatment was started, and all signs and symptoms improved gradually.